Implementasi Kriptografi Klasik Untuk Pengamanan Database Berbasis Web - Hidayatullah Sholihin; Herlina Latipa Sari; Hari Aspriyono (UNIVED Press, 2022)
Database is a fundamental component of an information system, where its development or use must be viewed from a broader perspective based on the needs of the organization. With the database all work becomes easier, both in data processing and viewing the output of the data. However, in addition to this convenience, it takes the security side of each record in the database to maintain data confidentiality. Implementation of Classical Cryptography in database security is made using the PHP Programming Language and MySQL Database. The classical cryptographic algorithm applied in this study is the Railfence Ciper Algorithm. Applications and application databases are uploaded online through the hosting domain https://kriptografihidayat.my.id/ and can be accessed from anywhere and anytime via the internet. Based on the tests that have been carried out, the results show that the application is able to secure the employee database in each storage field, and the functionality of the application runs as expected. The key used cannot be changed dynamically, but can be changed statically because it has been integrated into the program code to perform encryption and decryption on each input field. Record Table in the employee database that has been encrypted using the Railfence Ciper algorithm, so it cannot be read. Wireshark managed to capture the packet, but it was detected that there was an encryption process going on.